2017
DOI: 10.1111/bph.13913
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of phosphatidylinositol 4,5‐bisphosphate on cloned TMEM16A and TMEM16B channels

Abstract: Ca2+ -activated Cl À channels (CaCCs) are gated open by a rise in intracellular Ca 2+ concentration ([Ca 2+ ] i ), typically provoked by activation of G q -protein coupled receptors (G q PCR). G q PCR activation initiates depletion of plasmalemmal phosphatidylinositol 4,5-bisphosphate (PIP 2 ). Here, we determined whether PIP 2 acts as a signalling lipid for CaCCs coded by the TMEM16A and TMEM16B genes. EXPERIMENTAL APPROACHPatch-clamp electrophysiology, in conjunction with genetically encoded systems to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 79 publications
5
62
1
Order By: Relevance
“…Figure 1B summarizes this finding and shows ATP was critical for channel recovery. Our findings revealed that the PI(4,5)P2 dephosphorylation caused by Dr-VSP decreased TMEM16A activity in agreement with a recent report showing that exogenous PI(4,5)P2 increases TMEM16A activity whereas PI(4,5)P2 depletion has the opposite effect (Ta et al, 2017). …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Figure 1B summarizes this finding and shows ATP was critical for channel recovery. Our findings revealed that the PI(4,5)P2 dephosphorylation caused by Dr-VSP decreased TMEM16A activity in agreement with a recent report showing that exogenous PI(4,5)P2 increases TMEM16A activity whereas PI(4,5)P2 depletion has the opposite effect (Ta et al, 2017). …”
Section: Resultssupporting
confidence: 93%
“…PI(4,5)P2 stabilizes the current by preventing rundown but if PI(4,5)P2 is dephosphorylated then TMEM16A activity decreases. Our results are in agreement with those of Ta and co-workers showing that exogenous PI(4,5)P2 increases the activity of TMEM16A, but not TMEM16B in a Ca 2+ -dependent manner and activation of the Dr-VSP phosphatase inhibited TMEM16A (Ta et al, 2017). A previous report showed that adding diC8-PIP2 decreased the current through Ca 2+ -dependent Cl − channels activated by 500 nM Ca 2+ in inside-out patches excised from rat pulmonary artery cells (Pritchard et al, 2014); however, we do not have an explanation for this discrepancy.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations